2021
DOI: 10.3389/fped.2021.742916
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Quality of Grief and Bereavement Care in Pediatric Intensive Care Units Around the World, Opportunities for Improvement

Abstract: Pediatric Intensive Care Units (PICUs) provide multidisciplinary care to critically ill children and their families. Grief is present throughout the trajectory of illness and can peak around the time of death or non-death losses. The objective of this study was to assess how PICUs around the world implement grief and bereavement care (GBC) as part of an integrated model of care. This is a multicenter cross-sectional, prospective survey study. Questionnaires with multiple-choice and open-ended questions focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…44 These findings support the involvement of the palliative care team in providing longitudinal psychosocial-spiritual support to children and their families to improve overall quality of life, increase family satisfaction with care, and reduce health care utilisation. 7,47 Lastly, involving palliative care early allows time for the palliative care team to build rapport, and assess the needs and goals of the family while providing psychosocial support to the family and health care team through the disease's trajectory as well as at the end of life care especially considering that the mortality rates among children supported on extracorporeal membrane oxygenation are high. [48][49][50] None of the children who died within 48 hours of extracorporeal membrane oxygenation cannulation received a palliative care consultation, yet these children were in the hospital for at least 3 days prior to cannulation, providing a window of opportunity for early consultation.…”
Section: Discussionmentioning
confidence: 99%
“…44 These findings support the involvement of the palliative care team in providing longitudinal psychosocial-spiritual support to children and their families to improve overall quality of life, increase family satisfaction with care, and reduce health care utilisation. 7,47 Lastly, involving palliative care early allows time for the palliative care team to build rapport, and assess the needs and goals of the family while providing psychosocial support to the family and health care team through the disease's trajectory as well as at the end of life care especially considering that the mortality rates among children supported on extracorporeal membrane oxygenation are high. [48][49][50] None of the children who died within 48 hours of extracorporeal membrane oxygenation cannulation received a palliative care consultation, yet these children were in the hospital for at least 3 days prior to cannulation, providing a window of opportunity for early consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies outline the importance of providing grief and bereavement support to both the patient-family unit and the healthcare professionals (HCPs) involved. Such support is vital to allow healthcare professionals (HCP) to continue to provide ongoing high-quality EOL care ( 13 16 ). The international Paediatric Intensive Care Unit Model of Integrated Care study reported global disparities in PIC grief and bereavement care provision ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such support is vital to allow healthcare professionals (HCP) to continue to provide ongoing high-quality EOL care ( 13 16 ). The international Paediatric Intensive Care Unit Model of Integrated Care study reported global disparities in PIC grief and bereavement care provision ( 16 ). Despite individual national reports ( 6 , 8 , 14 ), there is no broad overview of contemporary EOL practice in European PIC though one study, performed over a decade ago, did investigate decision-making in the forgoing of life-sustaining therapy by PIC physicians and nurses ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations